2012
DOI: 10.3109/09537104.2012.675108
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of thrombelastography platelet mapping assay to measure the antiplatelet effect of P2Y12receptor inhibitors and high on-treatment platelet reactivity

Abstract: (2013) Usefulness of thrombelastography platelet mapping assay to measure the antiplatelet effect of P2Y 12 receptor inhibitors and high on-treatment platelet reactivity, Platelets, 24:2, 166-169,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…Recently, TEG has been widely used in the assessment of platelet function 21 22. However, few studies have investigated TEG parameters in patients undergoing extracranial or intracranial artery stenting for ischemic cerebrovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, TEG has been widely used in the assessment of platelet function 21 22. However, few studies have investigated TEG parameters in patients undergoing extracranial or intracranial artery stenting for ischemic cerebrovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…Previous results have suggested the predictive utility of measuring whole blood maximal clot strength in assessing risk for ischaemic events after coronary stenting, with significantly increased risk observed in patients within the highest quartiles of whole blood clot strength [2,7]. Although no direct comparison has been published between the positive predictive value of whole blood TEG and platelet reactivity testing, which has been well established in the identification of clopidogrel nonresponse after coronary stenting, the data available suggest similar utility [2,79]. Whole blood TEG-maximal clot strength comprises simultaneous contribution of plasma fibrin generation and platelet aggregation in the generation of a stable thrombus.…”
Section: Introductionmentioning
confidence: 99%
“…However, Jeong et al demonstrated a significant correlation between TEG and LTA in 730 patients treated by percutaneous coronary intervention. 18 Gurbel et al reported that the TEG MA parameters might be better than LTA in an in vivo situation because LTA ignored the important contribution of platelet-fibrin interactions to both thrombosis and hemorrhage. 15 We used TEG to test the effects of antiplatelet agents, and the proportion of resistance to clopidogrel (34.5%) in our series was lower than that reported by Lee et al (42.9%) in patients tested using VerifyNow.…”
Section: Discussionmentioning
confidence: 99%